The role of leadership style and work motivation on employee performance PT Paragon Technologi and Inovation - Sirojuddin, Ilham; Nuraulia, Fadila; Salsabila, Risa; Haryadi, Didit (International Journal of Applied Finance and Business Studies, 2024)
Among effective management systems, the importance of human resources is increasing. Employee performance is an essential factor influencing success. In an organization, this is one of the most critical functions of a company. This study aims to determine the variables that affect employee performance and develop a theoretical basis and research model. This study used an associative descriptive quantitative method with a population of 43 respondents drawn into a sample using non-probability sampling, saturated sampling / total sampling method—and data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis states that employee performance is influenced by leadership style, meaning that the higher the work motivation that employees have, the higher the performance of these employees. Thus, the second hypothesis states that work motivation is not able to give an increase in employee performance. The third hypothesis is that employee performance is influenced by leadership style and work motivation, which can simultaneously improve employee performance. This research is expected to make theoretical contributions to the literature in this context, certainly in the context of human resource management.